Representación gráfica de las marcas olfativas en Colombia a la luz de la Decisión 486 de 2000 de la Comisión de la Comunidad Andina (2019)
The purpose of the investigation is to analyze the compatibility of the graphic representation requirement established in article 134 of Decision 486 of 2000 and the olfactory Trademark. This, considering that, although this regulation establishes the possibility of registering odors as Trademarks, it also requires these signs to be susceptible of graphic representation. In this sense, bearing in mind the complexity inherent to scents, it aims to define whether, given the constitutive attributes of olfactory signs, as well as their disparities with traditional Trademarks, their registration would be a reality through a less rigorous analysis with respect to their graphic representation or through the modification of the communitarian norm.